A novel approach for in vivo DNA footprinting using short double-stranded cell-free DNA from plasma - Müller, Jan; Hartwig, Christina; Sonntag, Mirko; Bitzer, Lisa; Adelmann, Christopher; Vainshtein, Yevhen; Glanz, Karolina; Decker, Sebastian; Brenner, Thorsten; Weber, Georg F.; Haeseler, Arndt von; Sohn, Kai (Genome research, 2024)
Here, we present a method for enrichment of double-stranded cfDNA with an average length of ∼40 bp from cfDNA for high-throughput DNA sequencing. This class of cfDNA is enriched at gene promoters and binding sites of transcription factors or structural DNA-binding proteins, so that a genome-wide DNA footprint is directly captured from liquid biopsies. In short double-stranded cfDNA from healthy individuals, we find significant enrichment of 203 transcription factor motifs. Additionally, short double-stranded cfDNA signals at specific genomic regions correlate negatively with DNA methylation, positively with H3K4me3 histone modifications and gene transcription. The diagnostic potential of short double-stranded cell-free DNA (cfDNA) in blood plasma has not yet been recognized. When comparing short double-stranded cfDNA from patient samples of pancreatic ductal adenocarcinoma with colorectal carcinoma or septic with postoperative controls, we identify 136 and 241 differentially enriched loci, respectively. Using these differentially enriched loci, the disease types can be clearly distinguished by principal component analysis, demonstrating the diagnostic potential of short double-stranded cfDNA signals as a new class of biomarkers for liquid biopsies.
Online verfügbar: 13. September 2024
Gesehen am 16.04.2025